Transparent and Flexible Electromagnetic Interference Shielding Film Using ITO Nanobranches by Internal Scattering - Kim, Youngho; Hyeong, Seok Ki; Choi, Yeunji; Lee, Seoung Ki; Lee, Jae Hyun; Yu, Hak Ki (ACS Applied Materials and Interfaces, 2021)
A transparent and flexible film capable of shielding electromagnetic waves over a wide range of frequencies (X and Ku bands, 8-18 GHz) is prepared. The electromagnetic wave shielding film is fabricated using the excellent transmittance, electrical conductivity, and thermal stability of indium tin oxide (ITO), a representative transparent conductive oxide. The inherent mechanical brittleness of oxide ceramics is overcome by adopting a nanobranched structure. In addition, mechanical stability is maintained even after repeated bending experiments (200 »000 times). The produced transparent and flexible shielding film is applied to practical GHz devices (Wi-Fi and LTE devices), and signal sensitivity is confirmed to decrease. Therefore, it can be widely applied to various transparent and flexible electronic devices.
Keywords: Electromagnetic interference shielding; Flexible films; Indium tin oxide nanobranch; Internal scattering; Mechanically stable; Nanobranches; Shielding film; Thermally stable; Transparent films; X bands; electromagnetic interference (EMI) shielding; indium tin oxide (ITO) nanobranches; internal scattering; mechanically and thermally stable; transparent and flexible film